2021
DOI: 10.1002/alz.058497
|View full text |Cite
|
Sign up to set email alerts
|

Investigating auditory electrophysiological measures of participants with mild cognitive impairment and Alzheimer’s disease: A systematic review and meta‐analysis of event‐related potential studies

Abstract: Background: Objectively measuring auditory functions has been proposed as an avenue in differentiating normal age-related cognitive dysfunction from Alzheimer's disease (AD) and its prodromal states. Previous research has suggested auditory eventrelated potentials (AERPs) to be non-invasive, cost-effective and efficient biomarkers for the diagnosis of AD. The objective of this paper is to review the published literature on AERPs measures in older adults diagnosed with AD and those at higher risk of developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 80 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…A recent meta-analysis reported that higher processing of sensory information, as reflected by late latency AERPs N100 and P200, are impaired in those with AD when compared to healthy controls [ 204 ]. The N100 and P200 have been proposed to be produced by the primary and secondary auditory cortex, hence, changes in the appearance of these responses are thought to reflect measurable impairments in processing and perceiving variations in an auditory information [ 205, 206 ].…”
Section: Hearing Assessments As a Possible Diagnostic/screening Tool ...mentioning
confidence: 99%
See 3 more Smart Citations
“…A recent meta-analysis reported that higher processing of sensory information, as reflected by late latency AERPs N100 and P200, are impaired in those with AD when compared to healthy controls [ 204 ]. The N100 and P200 have been proposed to be produced by the primary and secondary auditory cortex, hence, changes in the appearance of these responses are thought to reflect measurable impairments in processing and perceiving variations in an auditory information [ 205, 206 ].…”
Section: Hearing Assessments As a Possible Diagnostic/screening Tool ...mentioning
confidence: 99%
“…Similar to results observed in behavioral CAP tests, particularly SSI-ICM, objective measures of discrimination, perception, and classification of auditory signals using N200 latency have also been shown to be delayed in those with cognitive impairment associated with AD [ 196, 204, 207 ]. The neural generators of the N200 peak include the auditory cortex and thalamic region [ 208, 209 ] and significant delays in the N200 latency have been observed in participants with MCI and those with AD [ 204, 207 ].…”
Section: Hearing Assessments As a Possible Diagnostic/screening Tool ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have also shown that ERP P300 can detect differences in P300 latency in people with a family history of AD as compared to age-matched controls [39,[54][55][56]. Additionally, results of several meta-analyses of ERP P300 latency studies in patients with AD and MCI support the use of ERP P300 as a biological marker for prodromal AD [57][58][59][60][61]. While most studies have reported a decreased P300 amplitude in patients with AD [62], there have been some exceptions, in which amplitude in patients with AD was reported as being equivalent to that in healthy controls [53,63].…”
Section: Erp In Dementiamentioning
confidence: 99%